Epiphrenic diverticula: An added source of complexity in achalasia management. Issue 3 (27th November 2019) - Holmes, Ian; Ko, Myung S.; Kouanda, Abdul; Singh, Aparajita; Nett, Andrew; Kathpalia, Priya
Abstract: Epiphrenic (pulsion) esophageal diverticula can occur in the setting of underlying esophageal motility disorders such as achalasia and present a unique management challenge to the gastroenterologist. Asymptomatic diverticula do not require treatment, but symptomatic diverticula require therapy targeted to the underlying esophageal motility disorder, or else the diverticula will recur. Generally, laparoscopic or combined laparoscopic/thoracoscopic myotomy, diverticulectomy, and anterior fundoplication are required. However, therapeutic options for epiphrenic diverticula are evolving as peroral endoscopic myotomy (POEM) becomes more commonplace. We review two cases of achalasia complicated by epiphrenic diverticula at our institution. In the first case, type II achalasia was identified and the patient underwent laparoscopic myotomy. In the second case, type III achalasia was present and the patient underwent successful POEM. We discuss the presentation, pathophysiology, and management of epiphrenic diverticula as well as the expanding role for POEM in diverticula. Abstract : Left: Esophagram in case 1. Right: Case 2 esophagram on postoperative day 1 following POEM.